Os peixes de um lago de várzea da Amazônia Central (Lago Janauacá, Rio Solimões) e suas relações com os crustáceos ectoparasitas (Branchiura: Argulidae) - Malta, Jose Celso de Oliveira (Acta Amazonica, 1984)
Atotal of one thousand three hundred and thihly five fish belonging to five orders, nineteen families and eighty species were caught in lago Janauacá, a floodplain lake, of the Amazon near Manaus. The natural infestation of Branchiura crustaceans on these fish was studied during a one year-period, March 1979 -March 1980. Fourteen species of Branchiura were collected and 11 percent of the fish were infected with, an average of5 parasites per host. The greatest infestations occurred in the Siluroids, with a prevalence Of 29% and a mean intensity of 18,5. Next were the Characoids with 8,4% and 2,5. The perciformes were third with 7,4% and 2,0. Few infestations occurred in the Osteoglossiformes, with 3,0% and 5,0 and in the Clupelformes, 4,0% and 1,0.Eighteen species offish were not parasitized by Branchiuna crustaceans. Taxonomic, biogeographical and commercial aspects of the fish are discussed.